Global health A challenge for interdisciplinary research - Kappas, Martin; Groß, Uwe; Kelleher, Dermot (Universitätsverlag Göttingen, 2012)
Human, animal and plant health is a field of work which offers opportunities for inter- and trans-disciplinary research. The whole topic bridges the natural and social sciences. Today, in a world of global environmental change it is widely recognized that human societies and their wellbeing depend on a sustainable equilibrium of ecosystem services and the possibility of cultural adaptation to global environmental change. The need to identify and quantify health risks related to global environmental change is now one of the most important challenges of humankind. Describing spatial (geographic, intra/inter-population) and temporal differences in health risks is an urgent task to understand societies' vulnerabilities and priorities for interventions better. The Göttingen International Health Network (GIHN) is a research and teaching network in relation to this cross-cutting topic. The book provides a collection of articles which contribute to this issue of overriding importance and presents an overview of the GIHN launch event.